Analysis of Laterally Loaded Piles in Undrained Clay Concave Slope. (23rd July 2021) - Jiang, Chong; Li, Xintai; Liu, Pan; Pang, Li
Abstract : A concave slope is a common type of slope. This paper proposes a simplified method to study the effect of a clay concave slope on laterally loaded piles. The hyperbolic p -y curve model is selected as the lateral pile-soil interaction model of the concave slope. Considering the two angles of the concave slope, the variation of the ultimate soil resistance with depth is divided into two parts, and the ultimate soil resistance varies nonlinearly with depth. The reduction factor method and normalization method are used to obtain the initial stiffness. The theoretical results will be compared with the calculation results of the 3D FE analysis to prove the rationality of this method. Finally, the simplified method is used to analyze the response of laterally loaded piles under different parameters.